"On Time and Discipline in Islam" (Analysis Towards Purpose of Islamic Education) - Dinasril Amir (AT-TA'LIM, 2014)
This article contains elucidation about punctuality issues and discipline in educational perspective. From the discussion that has been done it can be said that punctuality problems and discipline are very important and vital in building good and advanced of human life, because it is related to the basic, function and purpose of education as well as the teachings of Islam. Punctuality and discipline are a fundamental goal of the educational efforts and Islamic Shari'ah. In Islam, there are many concepts related to punctuality and discipline. They are obedience, self-control and behavior, submission and obedience, as well as support for the values and rules of the understanding, comprehension, awareness and responsibility. Being punctuality and discipline have to be owned and improved in education and life, and in turn, the family, society and the environment should support it in order to achieve the progress. Copyright © 2014 by Al-Ta'lim All right reserved